Nivel de satisfacción de los clientes en el centro deportivo Guaranda Crossfit. - Elizondo Icaza, Oscar Alberto (2023)
This sport designed to improve our physical and general skills, the whole body is worked in a balanced way which makes a difference from the gym where training through machines focuses on a certain muscle group. Crossfit is a high performance sport in which children, young people, adults, and older adults can participate in order to improve their health and improve their muscle mass, also with this type of exercises when resorting to the days will improve their level until reaching their maximum level of physical performance.